2022
DOI: 10.5194/acp-22-4355-2022
|View full text |Cite
|
Sign up to set email alerts
|

High atmospheric oxidation capacity drives wintertime nitrate pollution in the eastern Yangtze River Delta of China

Abstract: Abstract. Nitrate aerosol plays an increasingly important role in wintertime haze pollution in China. Despite intensive research on wintertime nitrate chemistry in recent years, quantitative constraints on the formation mechanisms of nitrate aerosol in the Yangtze River Delta (YRD), one of the most developed and densely populated regions in eastern China, remain inadequate. In this study, we identify the major nitrate formation pathways and their key controlling factors during the winter haze pollution period … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…These analysis over different time scales based on the multi‐year observations in urban Beijing suggest that the nocturnal O 3 plays a vital role in the nocturnal particulate nitrate formation through N 2 O 5 heterogeneous hydrolysis. Although the gaseous HNO 3 during daytime will also be converted into NO3 ${{\mathrm{N}\mathrm{O}}_{3}}^{-}$ at night, some literature demonstrated a very limited contribution of this pathway to nighttime NO3 ${{\mathrm{N}\mathrm{O}}_{3}}^{-}$ (Guo et al., 2018; Zang et al., 2022). Compared with gas‐phase OH + NO 2 conversion, the production efficiency of N 2 O 5 heterogeneous hydrolysis was more efficient and was the main source of nocturnal NO3 ${{\mathrm{N}\mathrm{O}}_{3}}^{-}$ pollution (Atkinson, 2000; H. Li et al., 2018; Y. Lin et al., 2020; P. Sun et al., 2018; Wen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These analysis over different time scales based on the multi‐year observations in urban Beijing suggest that the nocturnal O 3 plays a vital role in the nocturnal particulate nitrate formation through N 2 O 5 heterogeneous hydrolysis. Although the gaseous HNO 3 during daytime will also be converted into NO3 ${{\mathrm{N}\mathrm{O}}_{3}}^{-}$ at night, some literature demonstrated a very limited contribution of this pathway to nighttime NO3 ${{\mathrm{N}\mathrm{O}}_{3}}^{-}$ (Guo et al., 2018; Zang et al., 2022). Compared with gas‐phase OH + NO 2 conversion, the production efficiency of N 2 O 5 heterogeneous hydrolysis was more efficient and was the main source of nocturnal NO3 ${{\mathrm{N}\mathrm{O}}_{3}}^{-}$ pollution (Atkinson, 2000; H. Li et al., 2018; Y. Lin et al., 2020; P. Sun et al., 2018; Wen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the AOC would be underestimated in the winter if the contributions of Cl radicals to the photochemistry were ignored. In other words, the formation of secondary air pollutants, such as by oxidation of NO x to nitrate, SO 2 to sulfate, and VOCs to SOA, would be facilitated by the enhanced AOC in winter due to the participation of Cl radicals. On the other hand, Ma et al and Wang et al found that the VOCs consumed by OH radicals were crucial to O 3 formation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the traditional gas-phase chemistry in the Master Chemical Mechanism cannot effectively explain the rapid formation rates of the secondary aerosols observed during wintertime haze events in China, which suggests that an unknown mechanism for the AOC affects the formation of the secondary aerosols. On the other hand, model simulations usually underestimate the measured AOC at high NO x concentrations . This also indicates that the sources of atmospheric oxidants or the mechanism related to AOC might have been missed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because aerosol water content (AWC) is the precondition for triggering the nocturnal reactions (–), these reactions can play significant roles in NO 3 – formation on severe haze days under high relative humidity (RH) . However, the ground O 3 concentrations on severe haze days usually approach zero in the nighttime due to the fast titration of O 3 by NO, which can effectively suppress the in situ formation of NO 3 radicals and N 2 O 5 near the ground (–). Considering the relatively high concentrations of NO 3 radicals and N 2 O 5 aloft, the vertical mixing of the air aloft with the ground air in the early morning due to the breaking of the boundary layer was proposed to explain the relatively high contribution of the nocturnal reactions to ground NO 3 – .…”
Section: Introductionmentioning
confidence: 99%